2015
DOI: 10.1371/journal.pone.0138811
|View full text |Cite
|
Sign up to set email alerts
|

The Concordance between Patients’ Renal Replacement Therapy Choice and Definitive Modality: Is It a Utopia?

Abstract: IntroductionIt is desirable for patients to play active roles in the choice of renal replacement therapy (RRT). Patient decision aid tools (PDAs) have been developed to allow the patients to choose the option best suited to their individual needs.Material and MethodsAn observational, prospective registry was conducted in 26 Spanish hospitals between September 2010 and May 2012. The results of the patients’ choice and the definitive RRT modality were registered through the progressive implementation of an Educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 33 publications
1
49
0
3
Order By: Relevance
“…Overall, patients surveyed in 2015 and 2016 were very satisfied with the education process for RRT choice, with an average score of 8.5 out of 10, and differences between patients who opted for PD and those who chose HD were minimal (unpublished data) (see Table 1). This is in line with the previously mentioned research showing that free choice, assisted by PDAs, leads to an equal distribution of those choosing PD versus HD [20]. …”
Section: Gaddpe’s Strategic Action and Achievementssupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, patients surveyed in 2015 and 2016 were very satisfied with the education process for RRT choice, with an average score of 8.5 out of 10, and differences between patients who opted for PD and those who chose HD were minimal (unpublished data) (see Table 1). This is in line with the previously mentioned research showing that free choice, assisted by PDAs, leads to an equal distribution of those choosing PD versus HD [20]. …”
Section: Gaddpe’s Strategic Action and Achievementssupporting
confidence: 91%
“…Analysis of this registry showed a 50:50 split between patients choosing PD or HD plus an increase in pre-emptive transplantation choice. The use of PDAs, even with an unplanned start to RRT, achieved a high level of concordance between the chosen and final modality [20]. …”
Section: Gaddpe’s Strategic Action and Achievementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study from France, 47.5% choose PD, although data regarding patient choosing HHD were not reported (Keating et al 2014). In an intervention study based on shared decision-making, 50% chose dialysis at home (Prieto-Velasco et al 2015). The high number of patients in our study choosing dialysis at home could be explained by the fact that decisions regarding dialysis mode are highly personal and strongly influenced by patient and family values, the context of their life and a desire for minimal intrusiveness (Harwood & Clark 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous international studies have demonstrated that pre‐ESRD education leads to greater patient selection of home dialysis modalities . For example, a multicenter study conducted in Spain between 2010 and 2012 noted a prevalence of peritoneal dialysis therapy up to 47.8% among ESRD patients who received pre‐ESRD education compared to 6.5% among patients who did not receive the same education . Analogously, preemptive kidney transplantation was 1.5% and 0%, respectively.…”
Section: Renal Replacement Therapy Prevalence and Modalities In The Umentioning
confidence: 99%